Weeds for Cancer - Shah, Shruti (Homœopathic Links, 2015)
While studying the biological behaviour of cancer-specific remedies, it has been found that 90% of these remedies are prepared from weeds. There is a striking similarity between growth of weeds and malignant cells. This article contains the study of these weeds, their peculiar growth, spread and invasion mechanism. Therefore, according to doctrine of signature, homeopathic indications and modern phytochemistry, further research can be performed about usefulness of these weed remedies for treatment of cancer.
Keywords: cancer; weeds